Clinical case of malignant paraganglioma treatment involving carotid artery replacement with a prosthesis - D. R. Ibragimov; D. V. Yuldashev; T. M. Murasov; S. S. Kazbulatov (Опухоли головы и шеи, 2024)
One of the rare neuroendocrine vascular neoplasms is paraganglioma. This tumor is diagnosed in 0.5 % of all cases of head and neck tumors. The treatment of choice for paraganglioma is open surgical intervention. The number of complications after this surgery remains high. The rarity of paraganglioma dictates the necessity of personalized approach to each patient with this pathology.The article presents a clinical case of successful treatment of malignant paraganglioma. After open surgical intervention, control of the long-term results is necessary to prevent development of malignant process and disease recurrence.